2020
DOI: 10.1051/e3sconf/202020303009
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of electroplating wastewaters

Abstract: In this article, the specificity of wastewaters formed at electroplating plants and problem of its treatment is considered. The purpose of this research is to suggest the technological scheme of wastewater treatment, for one of the typical electroplating plants. Standard research methods were used: gravimetrical, photometrical and fluorimetrical methods of liquid analysis to achieve this goal. This article presents the method of electroplating wastewater treatment, based on chemical precipitation, including ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Electroplating is a harmful cause of ecological pollution resulting in the concentrations of heavy metals found in the largely formed wastewaters. It comprises of deposition of ornamental and shielding layers of metals and/or non-metallic surfaces which are dependent on the kind of technological processes involved (Belova, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Electroplating is a harmful cause of ecological pollution resulting in the concentrations of heavy metals found in the largely formed wastewaters. It comprises of deposition of ornamental and shielding layers of metals and/or non-metallic surfaces which are dependent on the kind of technological processes involved (Belova, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These effluents maybe consumed by unsuspecting persons leading to serious health complications and possibly loss of lives [2,3]. The deposition of contaminants into water bodies are dependent on the kind of technological processes involved [4]. The over-exposure of living system to metals and organic compounds discharged from industrial effluents have been reported to exhibit neurological, dermatitis impairment, delay in the physical, also mental development of children [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Although the solution for wastewater problems related to the electroplating industry have been analyzed in the literature [4][5][6], the increasing attention to sustainability issues calls for more environmentally friendly processes. Electroplating technology has recently Sustainability 2021, 13, 4453 2 of 11 been subject to investigation due to the high environmental impacts related to water pollution: electroplating wastewater contains highly toxic cyanide, cyanide complexes, and metal ions, making postproduction treatment a complex problem to be addressed by these companies [7,8].…”
Section: Introductionmentioning
confidence: 99%